Insiders and outsiders : Jewish and Gentile culture in Germany and Austria - Lorenz, Dagmar C. G. 1948- (Wayne State Univ. Press, 1994)
Insiders and Outsiders addresses various aspects of Jewish and Gentile interaction since the development of the German-Jewish literary and cultural identity in the early nineteenth century. Containing the work of prominent scholars, critics, and journalists involved with German-Jewish studies from around the world, this ambitious anthology of literary and cultural criticism suggests a reevaluation of important cultural and literary issues, including the problem of cultural diversity with regard to German-speaking countries and the question as to what constitutes German cultural identity in multicultural central Europe